Plan estratégico de marketing de la cooperativa construcción, comercio y producción de la ciudad de Quito. - Medina Ochoa, Richard Stalin (2017)
The objective of the present investigation is to carry out a strategic marketing plan for the Cooperativa de Credito y Credito, Comercio y Producción COOPCCP of the city of Quito, in such a way that a proposal is presented that allows the cooperative to develop and improve the offer of its products and services in the Quito market. For the preparation of this strategic marketing plan, methodological tools were considered such as: deductive, inductive, analytical and statistical. In addition to the application of techniques such as direct observation, survey and interview. The population under study was the 35,522 members of the COOPCCP, according to records from 2016 with a cut-off until December. Surveys were also applied to the 85 internal customers of the cooperative. The interview was made to the General Manager, Ing. Fernando Beltrán. In the evaluation made to the external factors of the COOPCCP through the matrix of Evaluation of External Factors EFE, the weighted result was 3.10, which means that the factors of opportunity are greater than those of threat. The evaluation of internal factors of the COOPCCP, carried out through the matrix of Internal Factors Evaluation EFI, gave as a weighted result 2.95 which means that the strengths of the COOPCCP have greater weight on the weaknesses of the same. Then, the SWOT matrix was elaborated based on the analysis of internal and external factors, where all the strengths, opportunities, weaknesses and threats present for the COOPCCP were visually determined. Once these factors were organized, the High Impact matrix was constructed, through which four strategic objectives were determined: 1) To accelerate the processes of granting credits in the COOPCCP. 2) Prepare an annual training plan for internal COOPCCP clients. 3) Implement the electronic channel for the COOPCCP. 4) Develop an advertising plan for the COOPCCP. The execution of the strategic objectives will entail a budget of $ 190,247.30 dollars. Finally, the conclusions and recommendations of this strategic marketing plan for the COOPCCP were presented.